RANCANGAN KENDARAAN TAKTIS PEMADAM KEBAKARAN HUTAN - Abdul Hafidh; Gihon Nugrahadi; Rully Suriatmadja; Ganal Rudiyanto (Lembaga Penelitian Universitas Trisakti, 2018)
Transportation has become an important part for human life, not least in Indonesia. People use transportation to support all aspects of life. Activities are supported by vehicles or means of transportation such as economy, education, social, and culture.Indonesia is no longer a country left behind and can’t be underestimated. With the already developed technology the country has been able to make real objects of transportation design by the nation's children. Although still pioneering but it can show great potential one day people are able to make a good transportation, in accordance with the special needs in Indonesia.Indonesia is a country with the biggest diversity of flora and fauna. Base on Food and Agriculture Organization of United Nation (FAO) in 2010 that Indonesia forest keeping 289 gigaton carbon and has crucial role on maintaining the stability of the world climate.Unfortunately, forest damage in this country are still apprehensive. Base on Ministry of Environment and Forestry of Indonesia, at least 1,1 million hectares or 2% from Indonesia forest shrink in every year.The biggest damage or threat to natural forest in Indonesia is illegal logging, forest fires, and exploitation either for residential development, industry, or encroachment as well. The damage wich getting worse causing disruption of the forest ecosystem stability and the surrounding environment.With technological advances and knowledge that this country had included understanding of every related authorities needs hopefully this design became new inovation that can support facilities and infrastructure forest fire management in Indonesia